FAMILY THERAPY UNTUK MEMBANGUN KELUARGA HARMONIS - Novita Eko Nardani; Purwoko, Budi; Al Habsy, Bakhrudin (Counseling Milenial (CM), 2025)
Family is the first place where a person learns to love, understand and feel understood. Having a harmonious family is based on good connection, honest and open communication, mutual respect and division of tasks carried out fairly by each family member. The existence of harmony is not determined by the adequacy of wealth, but also by emotional and spiritual harmony based on ethical and religious values. The study used the narrative review method, which is a form of literature review that aims to identify, summarize and analyze relevant literature in order to understand thoroughly the role of family therapy in building a harmonious family. The literature study conducted resulted in that family therapy includes important steps such as building rapport, developing emotional appreciation, giving behavioral assignments (home assignments), and strengthening counseling relationships. This intervention helps improve family ties, improve communication skills, and form healthy roles between husband, wife and children. Thus, family therapy can be a preventive and curative strategy in building a harmonious family towards the dynamics of life. The active involvement of all family members and the commitment to improve relationships are the main keys to success in building a harmonious family that is always healthy and happy.